Exposure to indoor air pollutants (PM10, CO2 And CO) and respiratory health effects among long distance express bus drivers - O., Mohd Firdaus; Jalaludin, Juliana (School of Health Sciences, Universiti Sains Malaysia, 2014)
Previous studies have consistently found that exposure to indoor air pollutants is higher inside buildings and buses. However, there are very few studies conducted in Malaysia related to indoor air pollutant in long distance express buses. The objective of this study was to determine the exposure of indoor air pollutants (PM10, CO2 and CO) and respiratory health problem among long distance express bus drivers. This cross sectional study was conducted among 30 long distance express bus drivers and the entire respondents were male. Exposure of PM10 was measured using DustTrak Aerosol Monitor, while CO2 and CO were measured using Q-Trak IAQ Plus. All parameters were measured along the routes where the average duration was four hours. A purposive sampling was used to select respondents based on inclusion and exclusion criteria such as aged 20 to 56 years old, at least one year working experience, no history of chronic lung diseases, and non-smokers. Questionnaire adapted from American Thoracic Society (ATS) was used to collect information on respondents’ socio-economic status, working history, and respiratory symptoms. Lung function tests were performed after the participants arrived at their destinations. Data collected showed that the mean concentration of PM10 (220.00±120.00µg/m3 ), CO2 (1085.50±460.98ppm), and CO (2.79±0.95ppm) were still below the permissible level according to indoor air guidelines by WHO. The number of passengers on the bus influenced the concentrations of elevated CO2 inside buses. Chronic respiratory symptoms, which were reported among drivers, were phlegm (23.3%), cough (20.0%), wheezing (13.3%) and chest tightness (10.0%). Lung function result showed that there were 50% respondents who had abnormality of FVC% value and FEV1% value. Exposure to air pollutants continuously over a long period while driving is potentially causing ill effects to drivers' respiratory health. Exposure to PM10 in air-conditioned buses such as long distance express buses can increase the risk of respiratory illness and the reduction of lung function among bus drivers. Therefore, control measures may be needed to improve these situations.